2005
DOI: 10.1177/0192512105055806
|View full text |Cite
|
Sign up to set email alerts
|

How Does Democratic Regime Change Affect Mass Political Ideology? A Case Study of South Korea in Comparative Perspective

Abstract: ABSTRACT. This article explores the ideological dynamics of democratic regime change in South Korea from a comparative perspective. Analyzing national sample surveys conducted during the first decade of democratic rule, we find that the democratization of the country's rightwing dictatorship has resulted in a movement of many South Koreans from the right to the left on the ideological spectrum. However, many of the South Koreans who have shifted their position on the spectrum have done so without changing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Thirdly, and perhaps most importantly, democracy itself may strengthen the sociological and attitudinal underpinnings of left–right orientations by allowing articulation and debate of issue positions from across the ideological spectrum (see Shin and Jhee, 2005). In contrast, authoritarian governments frequently restrict any such expressions except for ones buttressing the regime, and depict alternative ideologies as illegitimate, in effect curtailing the available ideological space open to contestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, and perhaps most importantly, democracy itself may strengthen the sociological and attitudinal underpinnings of left–right orientations by allowing articulation and debate of issue positions from across the ideological spectrum (see Shin and Jhee, 2005). In contrast, authoritarian governments frequently restrict any such expressions except for ones buttressing the regime, and depict alternative ideologies as illegitimate, in effect curtailing the available ideological space open to contestation.…”
Section: Discussionmentioning
confidence: 99%
“…This last set of factors, which may be especially pertinent in societies that have only recently transitioned from authoritarian rule, warrants some elaboration. Due to conflicts leading up to democratization, in new democracies ‘the democratic–authoritarian dimension may overshadow the classical conflict over issues of economic redistribution and define the central meaning of left and right’ (Moreno, 1999: 2), as ‘democratization of a right-wing dictatorship shifts the masses to the left, while the democratization of a left-wing dictatorship shifts them toward the right’ (Shin and Jhee, 2005: 394). The following paragraphs set out hypotheses regarding each of these variables.…”
Section: Data and Hypothesesmentioning
confidence: 99%
“…Analyzing eight West European democracies, Huber (1989) found that the partisan component does not generally dominate the issues component of these scales. More recently, studies have shown the substantive loading of the left-right scale in a variety of new democracies, including Russia (Evans and Whitefield 1998), South Korea (Shin and Jhee 2005) and other countries (Mainwaring and Torcal 2006). In this contribution, we start with the assumption that the left-right dimension does have a substantive meaning in all the elections analyzed -even though this substantive meaning may be limited to parts of the electorate with a higher education.…”
Section: Ideology and The Left-right Scalementioning
confidence: 99%
“…Notwithstanding the reality of North Korean threats, military-related ideological issues were often a bigger consideration in the decision to migrate. For more than 60 years both South Korean civil and military regimes have continuously promoted strong anti-communist ideas to the public, ‘proclaiming leftists as agents of the communist North’ (Shin and Jhee, 2005:382), and have used the left–right construct to challenge and to monitor the ideological positions of politically active citizens. For instance, South Korean politicians have frequently used ideological issues to strengthen their power and to whitewash major incidents such as political and corruption scandals (Shin and Jhee, 2005).…”
Section: Macro Societal Structure Risk and Individuals’ Decision To mentioning
confidence: 99%